2020
DOI: 10.1088/1757-899x/949/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Heritage Evaluation: restoration plan through HBIM and MCDA

Abstract: This study is prompted by the activity carried out within a EU funded project (WARMEST)[1] whose goal is to analyze monuments’ degradation due to factors such as climate change and growing number of tourists, create a model to describe and anticipate the phenomena, and put in place a user-friendly Decision Support System that will help in setting preventive maintenance plans. As part of the project, we had the chance to study in depth the degradation at the Patio de Los Leones, the core of the world-famous sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Ferraz et al (2016) [23] analyzed the literature related to building pathology detection technology and methods and concluded that there is currently no management system for quickly obtaining pathology information and that the importance of building a pathology information management system is emphasized. Acampa et al (2020) [24] used the HBIM model to analyze the aging factors and maintenance management of columns in the Patio de Los Leones in Alhambra, Spain. Israeli scholars used threedimensional laser scanning technology to collect data on the severely damaged walls of Jerusalem's historical buildings and drew flat, vertical, and cross-sectional views of the walls, which provided a data basis and repair plan for subsequent wall protection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ferraz et al (2016) [23] analyzed the literature related to building pathology detection technology and methods and concluded that there is currently no management system for quickly obtaining pathology information and that the importance of building a pathology information management system is emphasized. Acampa et al (2020) [24] used the HBIM model to analyze the aging factors and maintenance management of columns in the Patio de Los Leones in Alhambra, Spain. Israeli scholars used threedimensional laser scanning technology to collect data on the severely damaged walls of Jerusalem's historical buildings and drew flat, vertical, and cross-sectional views of the walls, which provided a data basis and repair plan for subsequent wall protection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several tools have been developed in the last decades to support decision-makers to assess the effectiveness and quality of retrofitting interventions, especially in the field of multicriteria evaluation methods [16]. Concerning design quality, several research studies have been carried out in Europe [17,18], especially in Italy, with the Siva-SISCo evaluation method [19,20], while EPiQR [21,22], developed at the EPFL, has been found particularly fitting to evaluate the environmental impact of retrofitting existing buildings.…”
Section: Strategies For Sustainable Regeneration Intervention: State-...mentioning
confidence: 99%
“…Subsequently they are validated on a case study so that their suitability or need for improvement can be evaluated [52], [56]. On other occasions, HBIM repositories are used to help in the decision-making process by defining hierarchies in the information levels that allow organizing the importance of deterioration and favoring the establishment of priorities [57].…”
Section: Hbim and Preventive Conservationmentioning
confidence: 99%